Empagliflozin-A Sodium Glucose Co-transporter-2 Inhibitor: Overview of its Chemistry, Pharmacology, and Toxicology - Yadav, Jyoti; Ahsan, Farogh; Panda, Prabhudatta; Mahmood, Tarique; Ansari, Vaseem A.; Shamim, Arshiya (Current Diabetes Reviews, 2024)
Background: Empagliflozin is a sodium glucose co-transporter-2 (SGLT2) inhibitor that has gained significant attention in the treatment of type 2 diabetes mellitus. Understanding its chemistry, pharmacology, and toxicology is crucial for the safe and effective use of this medication. Objective: This review aims to provide a comprehensive overview of the chemistry, pharmacology, and toxicology of empagliflozin, synthesizing the available literature to present a concise summary of its properties and implications for clinical practice. Methods: A systematic search of relevant databases was conducted to identify studies and articles related to the chemistry, pharmacology, and toxicology of empagliflozin. Data from preclinical and clinical studies, as well as post-marketing surveillance reports, were reviewed to provide a comprehensive understanding of the topic. Results: Empagliflozin is a selective SGLT2 inhibitor that works by constraining glucose reabsorption in the kidneys, causing increased urinary glucose elimination. Its unique mechanism of action provides glycemic control, weight reduction, and blood pressure reduction. The drug's chemistry is characterized by its chemical structure, solubility, and stability. Pharmacologically, empagliflozin exhibits favorable pharmacokinetic properties with rapid absorption, extensive protein binding, and renal elimination. Clinical studies have demonstrated its efficacy in improving glycemic control, reducing cardiovascular risks, and preserving renal function. However, adverse effects, for instance, urinary tract infections, genital infections, and diabetic ketoacidosis have been reported. Toxicological studies indicate low potential for organ toxicity, mutagenicity, or carcinogenicity. Conclusion: Empagliflozin is a promising SGLT2 inhibitor that offers an innovative approach to the treatment of type 2 diabetes mellitus. Its unique action mechanism and favorable pharmacokinetic profile contribute to its efficacy in improving glycemic control and reducing cardiovascular risks. While the drug's safety profile is generally favorable, clinicians should be aware of potential adverse effects and monitor patients closely. More study is required to determine the longterm safety and explore potential benefits in other patient populations. Overall, empagliflozin represents a valuable addition to the armamentarium of antidiabetic medications, offering significant benefits to patients suffering from type 2 diabetes mellitus. This study covers all aspects of empagliflozin, including its history, chemistry, pharmacology, and various clinical studies, case reports, and case series.
Keywords: diabetes mellitus